Enhancing Consumer Benefit Via Special Tax Scheme for Social Enterprise - Rabiatul Adawiyah binti Mohd Ariffin; Zuhairah Ariff Abd Ghadas; Shahril Nizam bin Md Radzi (Yuridika, 2023)
In Malaysia, social enterprises (SEs) are still in their infancy, but they are growing in popularity as more people become aware of the beneficial effects on local communities. SEs in Malaysia are business models that combine the aspects of both non-profit and commercial entities to achieve social or environmental objectives. Business organizations, such as partnerships, corporations, and limited liability partnerships, are used to operate SEs because there is no specific legal entity for SEs in Malaysia. From a Malaysian perspective, tax-exempt status is one of the main challenges encountered by Malaysian social entrepreneurs. Despite the government’s efforts to recognize SEs, the problem of taxation for SE has not been resolved because SE still must pay taxes in a manner similar to that of commercial entities. This study aims to provide tax benefits to SE in Malaysia. Although Malaysia revised its laws and accredited SEs, no tax exemption has been provided exclusively for SEs. SEs contributions are meant to improve social welfare, but SEs are not exempt from taxes, such as charitable organizations. SEs business methods and organizational structures, which are comparable to those of commercial companies, lead to the conclusion that SEs are comparable to commercial organizations. The research concludes that by introducing tax exemptions permanently for SEs in Malaysia, customers can benefit from supporting businesses that align with their values, while SEs can benefit from increased support and growth opportunities. Governments can also benefit from a stronger economy and increased social and environmental impacts, making this an attractive policy option for Malaysian society.